A Novel Role for Progesterone and Progesterone Receptor Membrane Component 1 in Regulating Spindle Microtubule Stability During Rat and Human Ovarian Cell Mitosis - Lodde, Valentina (Society for the Study of Reproduction, Inc., 2010)
The present studies were designed to assess the roles of progesterone (P4) and Progesterone Receptor Membrane Component 1 (PGRMC1) in regulating mitosis of spontaneously immortalized granulosa cells (SIGCs) and ovarian cancer cells, SKOV-3 cells. Because PGRMC1 has been detected among the proteins of the human mitotic spindle, we theorized that P4 and PGRMC1 could affect mitosis through a microtubule-dependent process. The present study confirms that SIGC growth is slowed by either P4 treatment or transfection of a PGRMC1 antibody. In both cases, slower cell proliferation was accompanied by an increased percentage of mitotic cells, which is consistent with a P4-induced prolongation of the M phase of the cell cycle. In addition, P4 increased the stability of the spindle microtubules, as assessed by the rate of beta-tubulin disassembly in response to cooling. Also, P4 increased spindle microtubule stability of SKOV-3 cells. This effect was mimicked by the depletion of PGRMC1 in these cells. Importantly, P4 did not increase the stability of the microtubules over that observed in PGRMC1-depleted SKOV-3 cells. Immunofluorescent analysis revealed that PGRMC1 is distributed to the spindle apparatus as well as to the centrosomes at metaphase. Further in situ proximity ligation assay revealed that PGRMC1 interacted with beta-tubulin. Taken together, these results suggest that P4 inhibits mitosis of ovarian cells by increasing the stability of the mitotic spindle. Moreover, P4's actions appear to be dependent on PGRMC1's function within the mitotic spindle.